VD_FINDINFO HC / 2013 / 241 vom 27. März 2013 - VD Tribunal cantonal (2013)
AGGRAVATION DE LA SERVITUDE, SERVITUDE, DROIT DE PASSAGE, DROIT DE PASSAGE NÉCESSAIRE | 694 CC, 738 CC, 739 CC, 316 al. 3 CPC (CH)